The Effect of Various Weedy Periods on Growth and Yield of Soybean in Agroforestry System with Kayu Putih - Joko Budi Santoso Nugroho; Endang Sulistyaningsih; Priyono Suryanto (Jurnal Ilmu Pertanian, 2017)
This study was aimed to detect the effect of various treatment periods of weedy on the growth and yield of soybean; and to determine the most appropriate time periods of weedy for soybean in agroforestry systems with kayu putih. The experiment had been conducted in Menggoran, BDH Playen, KPH Yogyakarta, Gunungkidul Regency, Special Province of Yogyakarta from February 28 to May 9, 2015. Randomized Complete Block Design (RCBD) with three blocks as replications waas applied  in this experiment. The treatments were weedy periods on 0, 14, 28, 42, and 56 days after planting (dap) and weed-free period on 0, 14, 28, 42, and 56 dap. The results showed that there were significant differences in the soil moisture content, root surface area, root length, chlorophyll content, root dry weight, shoot dry weight, dry weight of soybean seeds, and weed dry weight. The highest seed weight per hectare was found in weed-free until harvest treatment but it was not significantly different from weedy periods after 56 dap and weed-free after 14 dap. The effective periods of weedy time for soybean in agroforestry systems with kayu putih began at 28 dap - 56 dap.